External morphology of the immature stages of Neotropical heliconians: IX. Dione glycera (C. Felder & R. Felder) (Lepidoptera, Nymphalidae, Heliconiinae) - Vargas,Héctor A. (2014)
External morphology of the immature stages of Neotropical heliconians: IX. Dione glycera (C. Felder & R. Felder) (Lepidoptera, Nymphalidae, Heliconiinae). The biology of the Andean silverspot butterfly Dione glycera (C. Felder & R. Felder, 1861) is still poorly known. This species is restricted to high elevations in the Andes, where the immature stages are found in close association with species of Passiflora belonging to the section Tacsonia (Juss.) Harms, especially P. tripartida var. mollissima (Kunth), which is grown for subsistence by villagers. Herein we describe and illustrate the external features of the egg, larva and pupa of D. glycera, based on light and scanning electron microscopy.